Article Review on Vectran-Super Fiber from Thermotropic Crystals of Rigid-Rod Polymer - Derseh Yilie limeneh; Kelem Tiessasie Yilma (Journal of Engineering)
According to the economic and environmental perspective, multifilament Vectran, yarn spun from liquid crystal polymer, is important because of its quite simple processing during spinning in a wide range of injection moulding, extrusion moulding, and melt spinning. Vectran fiber is an aromatic polyester spun from a liquid crystal polymer in a melt extrusion process. This process orients the molecules along the fiber axis, resulting in a high tenacity fiber, and Vectran melts at 330°C. Heat treatment can improve and vary the tensile strength of Vectran fiber. On average, tensile strength for Vectran is 26 grams/denier (grouped as a high tenacity grade) and the strength of the fiber is maintained after several flexing and bending actions. Abrasion resistance of Vectran is even higher than a similarly sized aramid yarn. In addition, the original dimensions are maintained under variance of temperature with negligible creep and shrinkage. Vectran fiber, characterized by its golden color, high strength and modulus, thermal stability at high temperatures, low creep, and good chemical stability, can be used in many various industries starting from ropes and cables to profound sea survey and military products.